Biznesa mobilo platformu lietotņu izstrādes iespējas - Obsokovs, Mihails (Latvijas Universitāte, 2015)
Šis darbs ir veltīts biznesa mobilas platformas tehnoloģiju pētīšanai un salīdzinājumam. Šobrīd lieli uzņēmumi piedāvā vairākas mobilo lietotņu izstrādes tehnoloģijas un mehānismus. Platformas piedāvā dažādus mehānismus, sākot ar programmatūras izstrādātāja rīkkopam, kas piedāvā funkcionalitāti lietotnes integrēšanai ar platformu un beidzot ar tehnoloģiju, kas dod iespēju ātri izstrādāt lietotnes bez programmēšanas koda rakstīšanas. Darbā ietvaros ir plānots salīdzināt izvēlēto tehnoloģiju stiprākas un vājākas pusēs. Praktiskais piemērs ir paredzēts, lai dotu iespaidu par tehnoloģijas izmatošanu reālas dzīves scenārijā.

This work gives overview of selected enterprise platform solutions and makes a comparison. It gives an insight into the range of solutions available on current market and numerous approaches available for development either in the cloud or in the offline IDE using a SDK provided by the solutions vendor or solutions that allow development options using only drag-and -drop. I tried to identify the strengths and weaknesses of the solutions examined and to gain knowledge about how these solutions can be used in real life scenarios. This document gives an overview of Salesforce.com, IBM MobileFirst and SAP Mobile Platform enterprise platform solutions and makes a comparison. These platforms were selected, because according to Gartner Survey they are the most prominent mobile solutions on the market in 2014. The mobile platform is a solution that provides that provides tools for development, application maintenance and security of the applications by handling authorization, identity management and transport channel security. In this document I tried to cover the approaches for implementation of these requirements.
Enterprise Mobile Platform application development methods
Keywords: Datorzinātne